A review of the genus Criotettix Bolivar (Orthoptera: Scelimenidae) from China - Wei, Shizhen; Zheng, Zhemin; Deng, Weian (Zootaxa, 2007)
A total of nineteen species of Criotettix Bolivar occurring in China were systematically researched in this paper. Two species, Criotettix longinota sp. nov. and Criotettix nigripennis sp. nov. are described as new to science. Synonymy, distribution and a key to species are presented. The type specimens are deposited in the Institute of Zoology, Shaanxi Normal University, Xi’an, China.